Official sports sponsorship fortress vs ambush marketing attack: Investigating the impact on implicit and explicit brand knowledge. Issue 1 (5th February 2018) - Schmidt, Steffen; Limbach, Matthias; Langner, Sascha; Wiedmann, Klaus-Peter; Albertsen, Levke; Reiter, Philipp
Abstract : Purpose: The purpose of this paper is to assess the effectiveness of event-related sports sponsorship and ambushing activity using social media video advertising that aim to affect spectators' implicit and explicit brand information processing. Design/methodology/approach: A dual model of brand knowledge is used that considers the implicit and explicit information processing of marketing-induced brand messages. A web study was conducted prior to the 2014 FIFA World Cup. Each participant implicitly and explicitly evaluated either one sponsor brand or one ambush brand before and after watching the video advertisement (within-subject design). A Wilcoxon signed-rank test was used to evaluate each change of the pre-post testing scores. Findings: Implicit and explicit brand associations as well as brand behavior were partially affected by the short contact with the advertisements of sponsor brands and ambush brands. In this regard, the implicit association measurements were more sensitive to reveal changes in the brand knowledge structure than their explicit counterparts. Furthermore, sponsorship advertising was slightly more effective than ambush advertising. Originality/value: The current exploratory study evaluated for the first time the performance of event-related video advertisements that were originally released on social media of sponsor brands and ambush brands. The findings emphasize the necessary requirement of evaluating the implicit processing in addition to the explicit processing of sponsorship information to ensure a holistic evaluation of consumers' memory with regard to the effectiveness of a sponsorship activity.